Biosynthesis of Iron Oxide Nanoparticles Using Leaf Extract of Ruellia tuberosa: Mechanical and Dynamic Mechanical Behaviour Kevlar-Based Hybrid Epoxy Composites - L. Natrayan; Yenda Srinivasa Rao; Gayatri Vaidya; Sumanta Bhattacharya; S. Kaliappan; Pravin P. Patil; Prabhu Paramasivam (Bioinorganic Chemistry and Applications)
One of the more enticing, ecologically responsible, as well as safe and sustainable methodologies is eco-friendly nanomaterial synthesis. Vegetation materials will be used as reductants instead of toxic substances for synthesising nanoparticles. The current study used Ruellia tuberosa (RT) leaf extract digest to synthesise FeO nanomaterials, which were then characterised using XRD. Following that, microbially produced FeO molecules were mixed with a Kevlar-based polymeric matrix to study the blended consequences. To examine the interbreeding, the current experimental analyses were performed, including both static and dynamic mechanical characteristics. The addition of FeO nanofillers improved the elastic modulus, tensile strength, and storage modulus of the nanocomposite. Impact force uptake has been raised to a certain extent by the addition of nanoparticles. The findings of this research show that incorporating FeO nanofillers into Kevlar fabrics is a promising technique for increasing the mechanical characteristics of hybrid laminated composites. As per DMA evaluation, the sample without nanomaterials had a more volcanic lava response, which is a useful thing for body systems for missile use. Another critical aspect of a nanoparticles-filled nanocomposite that must be addressed is the relatively uniform scattering of padding as well as the development of interfacial adhesion in such a combination. The presence of FeO fillers in polymeric composites is confirmed by XRD analysis.